Impact of Inflation on Nutritional Intake and Health of Youth in Bangladesh - Nuruzzaman; Minhazur Rahman Rezvi; Farian Alam; Mojammel Hossen Rumman; Rafatul Islam; Abdullah Al Sohan; Shakila khanum; Shahriaz Ahmmed (Khazanah Sosial, 2025)
Bangladesh's economy has been experiencing increasing inflationary pressure in food prices in recent years. This study explores the nexus between price inflation and nutritional food consumption among youth and explains whether it impacts their health, mental health, and academics. This study used a mixed-method approach, collected survey data from 205 youth respondents, and conducted 10 IDIs with the respondents. This study found that inflation significantly impacts youth-quality food consumption. Lower-income and middle-income youth are most affected by food price hikes and have become used to negative adaptations, including reducing the quality of food consumption and skipping meals. The changes in dietary behaviour had a significant impact on the health status of the youth, which also led to health and mental health pressure. The Bangladesh government should take the lead in enacting strong policies that promote lower prices, increased productivity, and educating young people about the affordability of nutrient-rich meals.